The characterisation of the complete mitochondrial genome of Polygonatum Kingianum reveals recombination mediated by repeats associated with DNA replication - Aien Tao; Jing Tao; Zhengkun Gan; Yue Zhang; Chenglong Yin; Guihua Jiang (Scientific Reports)
Abstract Polygonatum kingianum Coll et Hemsl (P. kingianum) is recognized as one of the most valuable medicinal species, demonstrating a diverse range of bioactivities, including antidiabetic effects, reduction of blood lipids, anti-tumor properties, and hyperglycemic activity. However, the mitochondrial genome of P. kingianum has not yet been reported. Therefore, we sequenced and assembled the mitochondrial DNA (mtDNA) of P. kingianum. The results indicate that the mitochondrial genome possesses a multi-branched conformational structure. Further annotation of the mitochondrial genome reveals that it is 647,110 bp in length, containing a total of 35 distinct protein-coding genes, 22 tRNA genes, and 4 rRNA genes. The analysis of gene loss revealed that a total of seven genes were absent in the mitochondrial genome of P. kingianum. This includes six ribosomal protein genes (rpl2, rpl6, rpl10, rps7, rps8, rps11) and two succinate dehydrogenase genes (sdh3 and sdh4), as well as one pseudogene. Furthermore, Analysis of mitochondrial genome coding sequences of ten closely related species revealed a total of 24 shared genes. The Ka/Ks values of all shared coding protein genes are less than 1, indicating that these genes have undergone purification selection during evolution and their protein functions are relatively stable. In addition, codon studies on P. kingianum mitochondria showed 29 high-frequency codons (RSCU > 1). The preference for codon usage is influenced by mutations and natural selection, but mainly determined by natural selection. Furthermore, we identified 31 homologous fragments spanning both chloroplast and mitochondrial genomes and 585 C-to-U RNA editing sites were predicted in mitochondrial PCGs. The phylogenetic tree established a close relationship between P. kingianum and the 27 closely related species. To sum up, this study will contribute to the application of population genetics and evolutionary research in the genus Polygonatum and other genera in the Asparagales family.